Reflective Functioning and Symptom Specific Reflective Functioning: Moderators or Mediators? - Rudden, Marie G. (Psychoanalytic Inquiry, 2017)
Reflective functioning (RF) is the capacity for imaging one’s own mind and that of another—what might have contributed to the development of his/her difficulties and strengths, what might be motivating factors for his/her behaviors in the present. This capacity is measured by the RF scale. When researching psychodynamic psychotherapies that aim at alleviating the symptoms of specific disorders, it seemed prudent to adapt the RF scale to measure how subjects think about the psychological origin of their specific symptoms. This resulted in the panic-specific RF scale, since adapted for other disorders—bulimia, PTSD, depression—as the symptom-specific RF scales. Research that has begun to validate these scales is discussed, as well as research that is beginning to address whether RF or symptom-specific RF can moderate or mediate the success of psychodynamic psychotherapies.